Effective sources of powdery mildew resistance among spring bread wheat for the northwest of the Russian Federation - T. V. Lebedeva; A. N. Brykova; E. V. Zuev (Труды по прикладной ботанике, генетике и селекции, 2023)
Background. Bread wheat (Triticum aestivum L.) is one of the world’s main food crops. In Russia, its gross harvest in recent years has reached 21.079 million tons. Blumeria graminis is one of the most harmful diseases of bread wheat. Annual harvest losses can reach 10–30%. In Leningrad Province, powdery mildew appears almost every year on cereals. Development of cultivars resistant to powdery mildew is the most important trend in spring bread wheat breeding. Its progress is determined by new sources of effective resistance genes and their incorporation into promising spring bread wheat cultivars. The purpose of this work was to retest the seedling and adult resistance to powdery mildew in spring bread wheat accessions selected over a period of more than twenty years and redefine the effectiveness of disease resistance sources at the present time.Materials and methods. Since 2000, VIR has conducted a search for powdery mildew resistance among 1283 spring bread wheat accessions. The identified 36 sources of adult and seedling powdery mildew resistance were reevaluated in 2022. Field and laboratory studies into the resistance to the pathogen were performed according to VIR’s guidelines.Results and discussion. In 2022, field and laboratory studies of spring bread wheat cultivars revealed accessions with resistance to the pathogen in all phases of plant development. Six sources remained resistant to powdery mildew for 13–22 years, another six showed resistance for 7–12 years, and 8 cultivars were immune for 6 years. Resistance of 9 accessions identified for this trait in 2020 was confirmed.Conclusion. Field and laboratory research into the resistance of spring bread wheat accessions to the pathogen identified sources retaining seedling and adult resistance to the Leningrad population of powdery mildew for 7 years or more. These accessions are recommended for use in wheat breeding programs.